An Orchestration for Wind Band of Peter Klatzow’s From the Poets: Exploring a systematic approach to orchestration. - Feder, Arthur John (Stellenbosch : University of Stellenbosch, 2015)
Thesis (MMus) -- Stellenbosch University, 2010.